Theoretical exploration of the reactivity of cellulose models under non‐thermal plasma conditions—mechanistic and NBO studies. Issue 20 (7th June 2022) - Lamine, Walid; Guégan, Frédéric; Jérôme, François; Frapper, Gilles
Abstract: Mechanistic details of cellulose depolymerization by non‐thermal (atmospheric) plasma (NTAP) remains under‐explored given the complexity of the medium. In this study, we have investigated the reaction mechanism of glycosidic‐bond degradation triggered by reaction with hydroxyl radicals, considered as the principal reactive species in NTAP medium. In the first step of reaction sequence, H‐abstraction reactions by HO ‧ . radical on different CH sites of the pyranose ring were found to be non‐selective and markedly exergonic giving rise to a set of cellobiosyl carboradicals likely to undergo further reactions. We then showed that cellobiosyl carboradicals are protected against direct hydrolysis, no activation of the (1–4)‐ β ‐glycosidic bond being characterized. Interestingly, a simple homolytic bond cleavage allowed to obtain desired monomer. Among the 18 possible fragmentations, involving CC and CO bond breaking from cellobiosyl carboradicals, 14 transition states were successfully identified, and only three reaction pathways proved kinetically and thermodynamically feasible. Natural bond orbital (NBO) analysis was performed to shed light on electronic structures of different compounds.